Clinicopathological and prognostic significance of PD-L1 expression in sarcoma: A systematic review and meta-analysis. Issue 25 (June 2018) - Zheng, Chuanxi; You, Wei; Wan, Peng; Jiang, Xiaochun; Chen, Jinquan; Zheng, Yuchen; Li, Wei; Tan, Jifeng; Zhang, Shiquan
Abstract : Abstract: Programmed cell death-ligands 1 (PD-L1) is a key immune checkpoint protein and a promising therapeutic target for malignancy tumor immunotherapy. The prognostic value of PD-L1 in patients with bone and soft tissue sarcoma remains controversial. Therefore, this meta-analysis is conducted to evaluate the associations of PD-L1 expression with overall survival (OS), progression-free survival (PFS), and clinicopathological characteristics of sarcoma A comprehensive literature search of PubMed, Web of Science, Embase, and Cochrane Library was conducted for relevant studies. A total of 14 studies published from 2013 to 2017 were included. The pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were extracted from included studies to assess the association between PD-L1 expression and OS, PFS of patients with sarcoma. Other relevant data were extracted to evaluate the correlations of PD-L1 expression with risk and clinicopathological characteristics of sarcoma. Stata 12.0 software was applied to calculate the strength of association between PD-L1 expression and sarcoma. In total, 14 articles containing 15 independent studies and 1, 451 patients were included in this meta-analysis. We found that the high PD-L1 expression was associated with poorer overall survival (HR 1.27, 95% CI: 0.70–1.84 P = .000) and poorer events-free survival (HR 2.05, 95% CI: 1.55–2.70, P = .000) in bone and soft-tissue sarcoma patients. Additionally, we conducted subgroup analysis according to histology type, ethnicity, target of PD-L1 assessment, cutoff, the significant correlations with poor overall survival and events-free survival were also observed. In contrast none of the clinicopathological characteristics (gender, age, tumor site, tumor grade, tumor depth, tumor necrosis rate, metastasis, recurrence, chemotherapy, radiotherapy) was found to be associated with PD-L1 expression in our analysis. The findings from this meta-analysis indicate that PD-L1 expression might be a useful predicative factor of poor prognosis for patients with bone and soft tissue sarcoma.